CFD simulation study of multistage vertical axis wind turbine (VAWT) - Baharudin, Muhammad Azzrul Ashraff; Didane, Djamal Hissein; Batcha, Mohd Faizal Mohideen; Abdullah, Kamil; Mohammed, Akmal Nizam; ., Mas Fawzi (Penerbit UTHM, 2020)
Nowadays, the generation of energy from wind power has grown significantly as one of the most important renewable energy sources in the world today. In this study, the performance of a multistage vertical axis wind turbine (VAWT) has been assessed through 3D computational fluid dynamics (CFD) simulation approach based on K-omega shear stress transport (SST) models using the ANSYS Software. The inexpensive, omnidirectional, compact and easy to assemble Savonius rotor has been applied in this study along with the multistage-rotor concept. Multistage-rotor is where one stage of the rotor is placed on top of another stage of the rotor. The wind speed tested ranges from 5 m/s to 11 m/s at a tip-speed ratio (TSR) ranging from 0.2 to 1.0. The findings for torque and power with different operating wind speed demonstrated that as the wind speed increases at constant tip-speed ratio (TSR), the torque also increases; meanwhile, the torque coefficient decreases. However, when the wind speed increases along with the increasing TSR, the power generated increases. Meanwhile, the performance power coefficient has a directly proportional relationship with the TSR and an inverse relation with the wind speed tested.